Identification and comparative analysis of volatile components in peaches from four regions - HAO Mingyue (Guoshu xuebao, 2025)
[Objective] Peach is an important widely cultivated fresh fruit variety in China and can be classified into melting, non-melting, and stony-hard groups based on its flesh characters. Yangshan Shui Mi and Fenghua Shui Mi are two representatives of white fleshed and soft-melting peaches in the Jiangsu and Zhejiang province of China. They have a beautiful appearance, rich juice, and sweet and fragrant flavor. This study was carried out to identify the aroma components and content in these peaches from Jiangsu and Zhejiang provinces. [Methods] 12 samples from Wuxi, Jiangsu, Hangzhou, Zhejiang and Ningbo, Zhejiang province were collected with additional 16 white-flesh peaches from Zhengzhou, Henan province used as controls to detect their volatile compounds and content by using a headspace solid-phase microextraction combined with gas chromatography-mass spectrometry (HS-SPME-GC-MS). [Results] A total of 71 volatile components was detected under 7 categories: 8 alcohols, 10 aldehydes, 9 terpenes, 13 esters, 6 lactones, 9 ketones, and 16 other components. Among these samples, 1, 6, and 18 had the most types of volatile substances, with 43, 40, and 40 compounds detected, respectively. And samples 27, 11, and 3 had the fewest, with 25, 30, and 30 volatile compounds detected, respectively. However, in terms of absolute content of volatile substances, the three samples with lowest volatile substance content were 19, 21, and 17, all from Zhengzhou, Henan province, with contents of 23 112.24 µg·kg-1, 25 887.26 µg·kg-1, and 26 021.88 µg·kg-1, respectively. And the three samples with high volatile substance content were 3,11, and 2, Wuxi, Jiangsu and Ningbo, Zhejiang province, with contents of 62 102.04 µg·kg-1, 64 926.44 µg·kg-1, and 71 891.48 µg·kg-1, respectively. Among the seven major categories of volatile components, aldehydes accounted for the largest proportion, ranging from 13.72% to 63.84%. The main components were trans-2-hexenal, hexanal, benzaldehyde, and nonanal. The second group was lactones, accounting for 6.62%-48.34%, with the main components being γ-decanolactone and δ-decanolactone. And the following group were esters, accounting for 0.39% to 14.44%, with the main components being ethyl acetate, octanoic acid ester, and hexyl acetate. To compare the effects of climate environment and cultivation conditions on volatile compounds in peaches, this study compared and analyzed the components and contents of volatile compounds in samples from four regions. It was found that 52, 41, 41, and 62 volatile compounds were detected in Wuxi, Jiangsu, Hangzhou, Zhejiang, and Fenghua in Zhejiang province, and Zhengzhou in Henan province, respectively. The total volatile content of the sampled peach varieties was in the range of 23 112.24-71 891.48 µg·kg-1, with an average of 43 062.56 µg·kg-1. The average values in Wuxi, Jiangsu province, and Hangzhou, and Fenghua, Zhejiang province were 47 787.19 µg·kg-1,46 785.23 µg·kg-1, and 59 569.19 µg·kg-1, respectively, which were significantly higher than that in Zhengzhou, Henan province (36 761.48 µg·kg-1). The study found that the aldehydes in peach fruit samples from Zhengzhou, Henan province were significantly higher than those from the other three regions, reaching 42.99%. The major aldehydes identified included 2-hexenal, acetaldehyde, and nonanal. However, terpenes in samples from Zhengzhou, Henan province were significantly lower than from the other three regions, accounting for only 12.52%. Due to impact of different environments on volatile components in different regions, a common variety (Hu Jing Mi Lu) from different regions were chosen for comparative analysis. The results showed that linalool was the main volatile component in the peach, accounting for 24.22%. Next were γ-decanolactone, 2-hexenal, hexanal, 2-Butanone, 4-(2,6,6-trimethyl-1-cyclohexen-1-yl)-, and δ-decanolactone, accounting for 17.12%, 12.81%, 6.09%, 6.06%, and 5.36%, respectively. The remaining volatile components were all less than 5%. Linalool was lower in Hu Jing Mi Lu in Hangzhou, Zhejiang province compared to that in Wuxi, Jiangsu province and Zhengzhou, Henan province. And two lactones, γ-decanolactone and δ-decanolactone, were higher in Wuxi, Jiangsu than that in Hangzhou, Zhejiang and Zhengzhou, Henan regions. For different volatile components, this study also calculated the Odor Activity Values (OAVs) of each components according to the previous reported literature, and ultimately identified 25 aroma components, of which 20 had a higher OAV greater than 1. The largest contributor to aroma was linalool, followed by 2-butanone, 4-(2,6,6-trimethyl-1-cyclohexen-1-yl)-, trans-β-Ionone, hexanal, nonanal, γ-decalactone, and γ-dodecalactone, with an average OAV of over 100. And the others were octanal, ethyl caprylate, benzaldehyde, ethyl acetate, γ-octanolactone and δ-decalactone, and so on. [Conclusion] The results showed that the total amount of volatile compounds in peaches in Jiangsu and Zhejiang regions was relatively higher, as in samples 2,3, and 11. In terms of different aroma types, peaches from these regions, such as samples 9,12, and 3, contained higher levels of esters and lactones, while samples 3,6, and 10 contained more terpenes. These lactones, which present fruity and floral aromas, might be the reason for the rich flavor in peaches from Jiangsu and Zhejiang provinces. The study provide reference for selecting elite varieties for crossing breeding targeting improved quality of peaches in Jiangsu and Zhejiang provinces.